Roles of renal tubular epithelial cell injury related cytokines in chronic kidney disease - Chuan-ling Wang; Shi-qiu Zhang; Yan-wei Cao; Ji Li; Yong-jun Zhu (Editorial Department of Journal of Clinical Nephrology, 2024)
Due to various causes, chronic kidney disease（CKD） is characterized by chronic irreversible changes in the structure and function of kidney. The most common pathological manifestation is renal fibrosis. Many studies have demonstrated that injured renal tubular epithelial cells could release a large variety of cytokines to cause extracellular matrix deposition and promote the development of renal fibrosis during CKD. This review summarized the latest studies on the roles of renal tubular epithelial cell injury-related cytokines in CKD. It provided new concepts for clarifying the mechanism and exploring new treatments of CKD.